Surface Modification of Polymer Substrates for Biomedical Applications - Neděla, Oldřich; Slepička, Petr; Švorčík, Václav (Materials, 2017)
While polymers are widely utilized materials in the biomedical industry, they are rarely used in an unmodified state. Some kind of a surface treatment is often necessary to achieve properties suitable for specific applications. There are multiple methods of surface treatment, each with their own pros and cons, such as plasma and laser treatment, UV lamp modification, etching, grafting, metallization, ion sputtering and others. An appropriate treatment can change the physico-chemical properties of the surface of a polymer in a way that makes it attractive for a variety of biological compounds, or, on the contrary, makes the polymer exhibit antibacterial or cytotoxic properties, thus making the polymer usable in a variety of biomedical applications. This review examines four popular methods of polymer surface modification: laser treatment, ion implantation, plasma treatment and nanoparticle grafting. Surface treatment-induced changes of the physico-chemical properties, morphology, chemical composition and biocompatibility of a variety of polymer substrates are studied. Relevant biological methods are used to determine the influence of various surface treatments and grafting processes on the biocompatibility of the new surfaces-mammalian cell adhesion and proliferation is studied as well as other potential applications of the surface-treated polymer substrates in the biomedical industry.